Constructing Stance and Interpersonal Meaning in Mandarin Pop Lyrics: A Corpus-Pragmatic Analysis of Jay Chou’s Songs - Chang, Chen-An (Corpus pragmatics : international journal of corpus linguistics and pragmatics, 2026)
This study investigates the pragmatic functions of recurring linguistic patterns in Mandarin pop lyrics through a corpus-based analysis of Jay Chou’s discography. As a prominent figure in Mandopop, Chou’s lyrics provide a valuable case for examining how stance, identity, and emotional resonance are linguistically encoded. The Jay Chou Corpus (JCC), comprising 160 songs released between 2000 and 2023, was analyzed using #LancsBox and AntConc to identify frequent lexical items, collocations, and four-word lexical bundles. Results reveal a strong preference for verb phrase-based bundles involving personal pronouns and communication verbs such as shuo (“say”), which serve key interpersonal and emotive functions. Referential bundles often foreground spatial imagery, reinforcing place-based and experiential themes. Compared to studies on Western artists like Taylor Swift, Chou’s lyrics favor conversational verbs and direct address, creating a more interactive lyrical style. While similar to BTS in the use of verb phrase bundles, Chou’s lyrics show a greater tendency toward spatially oriented referential expressions. This study contributes to corpus pragmatics by demonstrating how formulaic language operates within Mandopop to construct interpersonal meaning and emotional appeal.